Molecular epidemiology of multiple drug resistant Acinetobacter baumannii from a major teaching hospital in Malaysia - Moghaddam, Mohammad Reza Babaei (2016)
Acinetobacter baumannii is a Gram-negative opportunistic coccobacilli, the most important agent in nosocomial infections with high mortality rate. Multidrug resistance in strains isolated from nosocomial infections, makes it difficult and sometimes impossible to treat. The aim of this study is to investigate the molecular epidemiology of Multiple Drug Resistant Acinetobacter baumannii (MDRAB) in a tertiary care hospital in Malaysia (UKMMC). During the study period a total of 18509 patients were admitted at different wards in the hospital. Among them, 122 patients were infected with MDRAB comprising 56.5% males and 43.5% were females. The highest number of infection was observed in medical ward (n=31, 25.4%), followed by ICU (n=30, 23.6%), surgery (n=28, 22.9%), orthopaedic (n=11, 9%), urology (n=6, 4.9%), neurosurgery (n=4, 3.2%), burn (n=3, 2.5%) All isolates were phenotypically and genotypically confirmed as A. baumannii. All 122 isolates were screened for 25 antibiotics. Among the 25 antibiotics tested, except for polymixin B, all isolates showed resistance to more than 3 antibiotics. Imipenem and meropenam showed 100% resistance. A total of 14 antibiotic resistance genes were screened. The resistances for genes ranged from 1.6 to 99.9% for different antibiotics such as quinolones (ParC 97.5%; gyr 97.5%), cephalosporin (TEM 95.9%; CTX-M 1.6%; PER 93.4%) and carbapenems (OXA58 84.6%; OXA51 99.2%, OXA23 97.5%, IMP 2.45%, NDM-1 1.6%). Antiseptics are commonly used for the management of MDR (multiple drug resistance) pathogens in hospitals. They play crucial roles in the infection control practices. Antiseptics are often used for skin antisepsis, gauze dressing, and preparation of anatomical sites for surgical procedure, hand sterilization before in contact with an infected person, before an invasive procedure and as surgical scrub. All 122 MDRAB isolates screened for the presence of antiseptic resistant genes QacA/B and QacE (Quaternary Ammonium Compounds) and susceptibility towards chlorhexidine (CLX), benzalkonium (BZK) and benzethonium (BZT). Eighty-nine (73%) isolates harboured QacE gene, while none were positive for QacA/B. The MIC ranged from 0.2 to 0.6 for CLX, 0.02 to 0.2 for BZK and 0.04 to 0.2 μg/mL for BZT. The highest number of QacE positive isolates were obtained from surgery (n = 24; 27%; p < 0.05), followed by medical ward (n = 23; 25.8%) and ICU (n = 21; 23.6%). Majority of the isolates from wound swabs (n = 33; 37%), T/aspirate (n = 16; 18%) and tissue (n = 10; 11.2%) harboured the QacE genes. Followed by antibiotic and antiseptic susceptibility testing, all isolates were subjected to genomic fingerprinting through pulsed field gel electrophoresis (PFGE) approach. Analysis demonstrated seven clusters (A-B-C-D-E-F and G) with a high level of diversity among different isolates and wards. The degree of resistance for 25 antibiotics was compared among all seven clusters and the results indicated a significant difference among these groups (p=0.019). The highest resistance was observed in cluster C (23.667 – carbapenems) while the lowest belonged to both clusters B (22.000 – cephalosporins) and F (22.000 – quinolones). Antimicrobial resistance pattern for different isolates with same resistance were in different clusters and the highest resistance was observed in three main antibiotic classes. QacE, QXA58 and PER had the highest variation. The range of frequencies for QacE was between 100% (cluster B) and 42.9 % (cluster F), and this range for OXA58 was between 94.4% (cluster A) and 28.6% (cluster F), and for PER was between 100% (cluster B) and 66.7% (cluster C). In other words, these three genes had higher variation among all samples and consequently more contribution to form these clusters. Biofilms and quorum sensing (QS) are two phenomena that are very important and crucial in helping the MDRAB to cling to the skin, mucosal, and surfaces of inanimate objects such as medical devices (ventilator and tracheal aspirate) in hospital environments. Biofilms are known to increase drug resistance in bacteria. Quorum sensing (QS) characteristic in bacterial allows it to monitor their population density through the production and sensing of small signal molecules known as auto inducers. In MDRAB auto inducers are acyl-homoserine lactones (AHLs), (Chenia, 2013). The strong association between antibiotic resistance genes and QS through signalling pathway has been well established. In the present study, biofilm formation in selected highly resistant MDRAB isolates were analysed and were screened for the QS abaΙ gene. The biofilm formation increased 2-4 folds in resistant MDRAB and were significantly higher compared to the control Escherichia coli strain.